DIGITAL LITERACY AND ITS IMPACT ON CRITICAL THINKING AND WRITING SKILLS : A QUALITATIVE STUDY IN A HIGH SCHOOL CONTEXT: English - Febby Puspita Sari; Rahmat Budiman; Widya Rizky Pratiwi (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2025)
Thinking critically is an important literacy skill in education. With technology, students are able to analyze information more thoroughly, compare varying viewpoints, and collaborate more deeply. This study investigated how English digital literacy fosters critical thinking in eleventh-grade students at SMA Kusuma Bangsa Palembang. A qualitative case study design was performed on 16 eleventh-grade students and two Advanced-English course teachers who were selected using purposive sampling methods. Data were obtained through document analysis, semi-structured interviews, and classroom observation, and then were analyzed thematically to identify prevalent practices and perceptions. The results showed that students improved their reasoning skills while assessing the reliability of sources, consulting their teachers and peers, and utilizing various digital tools including Google Scholar, Grammarly, and ChatGPT. Engaging with digital texts also assisted them in identifying key ideas and improving overall comprehension.